Small bowel transplantation in rats, a multicenter experience summarizing the pitfalls to be overcome - Stringa, Pablo Luis (2016)
Small Bowel transplantation in rats is a highly complex microsurgical procedure because several technical complications may lead to recipient mortality and transplant failure. Our aim was to report the most common complications associated with orthotopic and heterotopic intestinal transplantation in rats in order to identify the “pitfalls” of the procedure and prevent them. A retrospective multicenter study was performed. All participant centers have established rodent transplant procedures and trained surgeons. Two hundred ninety-three complications from 264 unsuccessful intestinal transplants were reported, representing an overall failure rate of 15% of the procedures performed. Recipient complications were most frequent than donor (257 vs. 36 p<0.0001). Excessive surgical time (11/36); severe hemorrhage (12/36) and inappropriate infusion of the preservation solution in the intestinal graft (11/36) were the most common donor complications. Arterial anastomosis bleeding (50/257), venous anastomosis bleeding (35/257) and portal vein stenosis (26/257) were the most common intraoperative complications in the recipient. To maximize success rate, surgeons should optimize time and avoid bleeding during graft dissection in the donor surgery. After performing a bloodless vascular anastomosis an adequate post-operative management of the animal is mandatory to guarantee survival.